Droupadi Murmu: The Epitome of Transformative Leadership Excellence - A Global Theoretical Analysis of India's Most Deserving President - Pallathadka, Harikumar; Roy, Parag Deb (Stallion Journal for Multidisciplinary Associated Research Studies, 2025)
This comprehensive analysis presents Droupadi Murmu as an exemplary leader whose extraordinary journey from a tribal village to India's highest constitutional office represents the pinnacle of democratic achievement and leadership excellence. Through the integration of over twenty global leadership theories spanning Western and Eastern philosophical traditions, this paper demonstrates how Murmu embodies the highest ideals of transformative, authentic, ethical, and spiritual leadership while simultaneously revolutionizing federal governance excellence. Her remarkable trajectory—from overcoming profound personal tragedies to breaking centuries-old barriers of caste, class, and gender—exemplifies universal principles of leadership that transcend cultural boundaries. This analysis applies multiple theoretical frameworks including Transformative Federal Leadership (Pallathadka & Roy, 2025), Authentic Leadership Theory (Avolio & Gardner, 2005), Spiritual Leadership Theory (Fry, 2003), Ethical Leadership (Brown et al., 2005), Cultural Intelligence (Earley & Ang, 2003), Indigenous Knowledge Systems (Smith, 2012), and Eastern philosophical frameworks including Dharmic Leadership and Gandhian principles. The paper conclusively establishes that Murmu represents not merely a symbolic appointment but the most qualified, deserving, and transformational president in India's history—a beacon of hope demonstrating that true leadership emerges from service, resilience, and an unwavering commitment to uplifting the marginalized while maintaining the highest standards of constitutional integrity.